2006
DOI: 10.1111/j.1440-1789.2006.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of Creutzfeldt–Jakob disease with Met/Val heterozygosity at codon 129 and type 1 protease‐resistant prion protein presenting some florid‐type plaques and many Kuru plaques in the cerebellum

Abstract: We report an atypical case of CJD. The clinical course was similar to a classic CJD phenotype, but histopathological study revealed several florid-type plaques in the amygdale and abundant Kuru plaques in the cerebellum that are atypical of classic CJD. Molecular analysis showed methionine/valine heterozygosity at codon 129 and no pathogenic mutation in the coding region of the prion protein gene. Western immunoblots revealed type 1 protease-resistant prion protein (PrPres), and a ration analysis of PrPres sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The deposits of amyloid plaques may also be noticed in 5-10% of cases [28,30]. On the basis of clinicopathological findings, different variants of sCJD have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The deposits of amyloid plaques may also be noticed in 5-10% of cases [28,30]. On the basis of clinicopathological findings, different variants of sCJD have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Within some molecular subtypes, additional pathological variants have been reported such as MM, VV and MV1 patients with amyloid plaques (Hauw et al. 2000; Kawauchi et al. 2006; Lo et al.…”
Section: Sporadic Creutzfeldt‐jakob Disease: From Biochemical Complexmentioning
confidence: 99%
“…However, increasing evidence has now indicated that the nosology of sCJD is probably more complex. Within some molecular subtypes, additional pathological variants have been reported such as MM, VV and MV1 patients with amyloid plaques (Hauw et al 2000;Kawauchi et al 2006;Lo et al 2006;Kobayashi et al 2008) and there are important phenotypic variations among patients of the same molecular subtype at the clinical and pathological levels, including the level of neuronal loss and the aspect of PrP deposits (Faucheux et al 2009(Faucheux et al , 2011. At the biochemical level, several reports have documented a higher level of complexity for molecular typing results in sCJD.…”
Section: Open Questions Concerning the Variant Creutzfeldt-jakob Epidmentioning
confidence: 99%
“…Zu den unwahrscheinlichen Fällen werden neurologisch auffällige Patienten zugeordnet, die die genannten Kriterien nicht erfüllen. Die klassische Trias der sCJD, eine Kombination aus Demenz, Myoklonus und Periodic-Short-Wave-Komplexen (PSWC) im EEG, findet man in 2/3 aller sCJD-Fälle (Masters et al 1979; (Belay 1999, Kawauchi et al 2006, die bezüglich der sCJD ausschließlich mit diesem Genotyp assoziiert werden (Parchi et al 1996;Hill et al 1999b;Kretzschmar 2001). Der vierthäufigste MM2-Phänotyp spaltet sich in einen kortikalen und thalamischen Phänotypen, wobei der erstere große konfluierende Vakuolen mit perivakuolären Ablagerungen zeigt und der letztgenannte sich neuropathologisch nicht von der FFI unterscheidet.…”
Section: Scjd -Diagnostikunclassified